2018
DOI: 10.1017/s0890060417000634
|View full text |Cite
|
Sign up to set email alerts
|

AI EDAM special issue: advances in implemented shape grammars: solutions and applications

Abstract: This paper introduces the special issue “Advances in Implemented Shape Grammars: Solutions and Applications” and frames the topic of computer implementations of shape grammars, both with a theoretical and an applied focus. This special issue focuses on the current state of the art regarding computer implementations of shape grammars and brings a discussion about how those systems can evolve in the coming years so that they can be used in real life design scenarios. This paper presents a brief state of the art … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Each grammar includes an initial shape and a single shape rule, and the paper has focussed on identifying fixed part structures necessary to accommodate repeated application of the rule. Reducing shape representations to a set of fixed parts is a common strategy which can potentially simplify the difficulties inherent in implementing shape grammars [5,17]. However, this paper has shown that fixing the parts of shapes can make it impossible to fully implement shape computations, which includes recognition of emergent shapes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Each grammar includes an initial shape and a single shape rule, and the paper has focussed on identifying fixed part structures necessary to accommodate repeated application of the rule. Reducing shape representations to a set of fixed parts is a common strategy which can potentially simplify the difficulties inherent in implementing shape grammars [5,17]. However, this paper has shown that fixing the parts of shapes can make it impossible to fully implement shape computations, which includes recognition of emergent shapes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, since X < ½Y the structure of X embedded in Y is analogous to the structures illustrated in Figure 7a, so Y = XVYXX = PPVYXPP. 5. When ⅟7(6 -2√2)Y < X < ½Y then √½Y < d < ⅟7(4 + √2)Y and ⅟7(3 -√2)Y < P < (1 -√½)Y.…”
Section: Consequences Of Changing the Spatial Arrangementmentioning
confidence: 99%
See 3 more Smart Citations